KUALITAS BUTIR SOAL ASESMEN FORMATIF MATERI BILANGAN BULAT - Kristina, Ajeng; Suciati, Suciati; Darmayasa, Jero Budi (Mathematics Education And Application Journal (META), 2024)
The aim of this research is to explore the quality of formative assessment of integer material using descriptive quantitative research. The quality of test item is reviewed based on the attributes of validity, reliability and item characteristics. Proving content validity uses Aiken's V, while the reliability coefficient estimation uses Cronbach's Alpha. estimation of item parameters using classical test theory assisted by ITEMAN 4.3 software. Based on the validation results, 11 of the 20 test items met the valid criteria, while the other items were invalid. The assessment instrument has high consistency in terms of the reliability coefficient of 0.797. The results of the item parameter estimation show that as many as 19 items have a level of difficulty that is in the medium category or stated to be good, because the level of difficulty lies in the interval 0.31-0.70. Based on the distinguishing power parameter, the eight test item were able to differentiate between high ability test taker and low ability (rpbis 0.30). Judgig from function of the distractor/distractors, the 14 items of the distractor answer distribution test functioned well (Prop.Endorsing = 0.05). The fulfillment of the item quality criteria in the formative assessment instrument shows that the instrument can be applied to monitor the development of students' learning procesess, because the instrument is able to provide reliable information regarding students' needs in whole number material and is able to describe students' abilities well.Keywords : Formative Assessment, ITEMAN. and Item QualityTujuan dari penelitian ini adalah untuk menelusuri kualitas asesmen formatif materi bilangan bulat dengan menggunakan jenis penelitian kuantitatif deskriptif. Kualitas butir tes ditinjau berdasarkan atribut validitas, reliabilitas, dan karakteristik butir. Pembuktian validitas isi menggunakan V Aiken, sedangkan estimasi koefisien reliabilitas menggunakan alpha cronbach. Estimasi paramater butir menggunakan teori tes klasik berbantuan software ITEMAN 4.3. Berdasarkan hasil validasi, 11 dari butir 20 butir tes memenuhi kriteria valid, sedangkan butir lainnya tidak valid.  Instrumen asesmen memiliki konsistensi yang tinggi ditinjau dari koefisien reliabilitas sebesar 0,797. Hasil estimasi parameter butir menunjukkan sebanyak 19 butir soal tingkat kesukarannya berada pada kategori sedang atau dinyatakan baik, karena tingkat kesukaran terletak pada interval  0,31–0,70. Berdasarkan parameter daya pembeda, delapan butir tes mampu membedakan kemampuan peserta tes yang tinggi dan kemampuan rendah (rpbis 0,30). Ditinjau dari keberfungsian pengecoh/distraktor, 14 butir tes sebaran jawaban pengecohnya berfungsi dengan baik (Prop.Endorsing . Terpenuhinya kriteria kualitas butir pada instrumen asesmen formatif menunjukkan bahwa instrumen tersebut dapat diterapkan untuk memantau perkembangan proses pembelajaran peserta didik, karena instrumen mampu memberikan informasi yang terpercaya mengenai kebutuhan peserta didik pada materi bilangan bulat dan mampu menggambarkan kemampuan peserta didik dengan baik.Kata Kunci: Asesmen Formatif, ITEMAN, dan Kualitas Butir